La nupcialidad durante la década de los ochenta en Cuba - Catasús Cervera, Sonia (El Colegio de México A.C., 1992)
This study presents an analysis of the demographic characteristics, levels and tendencies followed by Cuban nuptiality during the 1980's. The author uses the data provided by the 1987 "Encuesta Nacional de Fecundidad" (National Survey on Human Fertility) and data recorded in the last Cuban census, taken in 1981, to evaluate the changes experienced by women of fertile age of various marital status-primarily those in legal marriage and consensual unions-, highlighting the differences between the two. The study also takes into consideration peculiarities presented by women living in either of the two marital groups, analyzing the two in terms of various socioeconomic attributes, such as: level of education, labor status, and ocupational category. As a final point, the author analyzes the process of marital dissolution -whether legal or not- as it takes place within that sector of the female population.